EFL Students’ Perceptions of Reading Electronic Books - Jona Dinita Islami; Silih Warni (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2020)
This article investigated EFL students’ perceptions of reading e-books. A questionnaire was employed in this research, containing twelve-item questions of perceptions and the use of e-book plus seven demographic questions. The link of questionnaire was distributed through social media, and 100 participants joined the research. The data was analyzed and themed in six parts, 1) use, awareness and purpose of e-book, 2) comparison with printed books, 3) use and satisfaction of library service, 4) library supports of e-books, 5) advantages and disadvantages of e-books, and 6) catch-all question. The result showed that most participants were generally satisfied with e-books; however, they still preferred the printed book because of some issues. Little availability of e-books in the university library also became one of the reasons why they still preferred regular book and considered e-books only as complements. Key Words: EFL, E-book, Perception